Personal and organizational reputation, a matter of trust! - Miranda, Sandra (2019)
The study of personal reputation only recently gained space and visibility in the field of organizational studies. For this, much progress has been made in organizational reputation, which structurally similar in genesis, provides the guidelines and identifies similar processes on how organizational actors develop and use individual reputation to have influence and maximize their effectiveness (Tsui, 1984; Ferris, Blass, Douglas, Kolodinsky and Treadway 2003). Following the challenges of literature, the main objective of this research is to understand how personal reputation influences organizational reputation, predicting the mediating effect of the organizational trust.